تأثير الانمي على الشباب والمراهقين - عثمان عبد النور (كلية العلوم الاجتماعية, 2023)
. This study examines the impact of anime films on young people and adolescents, where the contents of these films are analyzed and how they affect the behaviour, beliefs and personality of followers. The study indicates that some content of anime films can be harmful and adversely affect followers, and warns against exposure to these contents. It is worth noting that these films are very popular among young people and adolescents and can be used to spread positive messages and improve their impact on followers. In addition, studies suggest that anime films can help develop followers' creativity and imagination and motivate them to think critically and innovate. It also exposes followers to new cultures and ideas, and helps them expand their horizons and better understand the world. It is important to emphasize the need for followers to be guided to enjoy the anime films correctly and to monitor what they are watching, and to identify the limits necessary to avoid negative impact on them. Some studies suggest that anime films can help promote followers' human and moral values, such as friendship, cooperation, altruism and tolerance. These values are essential in building healthy and coherent societies. It is also important to emphasize the need to provide alternatives to anime films with harmful content, such as educational films, documentaries, sports and music films, etc., in order to achieve diversity and balance in the followers' experience. Finally, it can be said that studying the impact of anime films on young people and adolescents is an important topic that deserves attention and careful analysis
Keywords: الانمي